Effect of low-load and low-volume squat training combined with plyometrics during a full season on physical performance in young soccer players - Franco-Márquez, F.; Serrano-Cañadillas, C.; Yáñez-García, J. M.; González-Badillo, J. J.; Rodríguez-Rosell, D. (Sports, 2025)
The aim of this study was to analyze the effects of a 24-week low-load, low-volume resistance training (RT) program combined with plyometric exercises on the physical performance of U-15 male soccer players. Thirty-two young soccer players were divided into a strength training group (STG) and a control group (CG). The STG added two RT sessions per week—using moderate loads (45-60% 1RM) and a low number of repetitions per set—combined with plyometrics to their regular soccer training, while the CG continued with only the field soccer training. Performance assessments (a running sprint test, a countermovement jump, and a progressive loading test in a full squat exercise) were conducted before and after each of three 8-week periods. Significant `time × group` interaction in favor of STG was observed for T20 (p < 0.05), CMJ (p < 0.001), and all variables (p < 0.001) assessed during the full squat exercise. Significant changes between groups were observed in T10 (Post 1 and Post 3, p < 0.05), CMJ (Post 1, Post 2, and Post 3, p < 0.05-0.001), and all strength variables (Post 1, Post 2, and Post 3, p < 0.05-0.001). The findings of this study suggest that a training program based on weightlifting with light loads for a few repetitions per set combined with jumps and sprint exercises, in addition to regular soccer training, induces greater and earlier improvements in strength and sport-related actions (jumping and sprinting), compared with only field soccer training. Coaches and strength-conditioning coaches should consider using RT with low loads and low volume and performing each repetition as fast as possible as an effective stimulus to improve physical performance in key match-determining actions efficiently.